2017
DOI: 10.1039/c6ra25339c
|View full text |Cite
|
Sign up to set email alerts
|

The role of intrinsic vacancy defects in the electronic and magnetic properties of Sr3SnO: a first-principles study

Abstract: In this study, we use first-principles electronic structure calculations to investigate the structural, electronic and magnetic properties of pristine and intrinsic vacancy containing Sr 3 SnO inverse perovskite. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…We chose the muffin-tin radius (RMT) of each atom to be RMT Sr = 2.41, RMT Sn = 2.5, and RMT O = 2.41 in the unit of the Bohr radius a 0 . We set the plane-wave cut off as RK max = 8, the highest angular momentum as l max = 10, maximum magnitude of the largest vector in charge density Fourier expansion as G max = 18, and the separation energy between the valence and core states as −7.0 Ry [20]. Only when estimating the energy of the local lattice vibrations in the hypothetical superstructure "Sr 2 Sn 2 O 2 ," we used the separation energy of −6.0 Ry in order to avoid a technical problem.…”
Section: E First-principles Calculationmentioning
confidence: 99%
“…We chose the muffin-tin radius (RMT) of each atom to be RMT Sr = 2.41, RMT Sn = 2.5, and RMT O = 2.41 in the unit of the Bohr radius a 0 . We set the plane-wave cut off as RK max = 8, the highest angular momentum as l max = 10, maximum magnitude of the largest vector in charge density Fourier expansion as G max = 18, and the separation energy between the valence and core states as −7.0 Ry [20]. Only when estimating the energy of the local lattice vibrations in the hypothetical superstructure "Sr 2 Sn 2 O 2 ," we used the separation energy of −6.0 Ry in order to avoid a technical problem.…”
Section: E First-principles Calculationmentioning
confidence: 99%
“…Theoretically, it has been proposed that Sr 3− x SnO can host topological superconductivity, reflecting its unusual normal-state electronic states 6,17 . More recent theoretical calculations predict various properties and deficiency effects in antiperovskite oxides, including those of Sr 3 SnO 1820 . Furthermore, it was shown that, in Sr 2.5 SnO in different deficiency arrangements, the Fermi level still lies in bands with strong mixing between the Sr-4 d and Sn-5 p orbitals 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The antiperovskite Dirac metal oxides (ADMOs), in which metal ions have negative valence states [1], exhibit some unusual physical properties such as superconductivity [2][3][4], topological behavior [5], ferromagnetic behavior [6][7][8][9][10] and thermoelectric transport properties [11,12]. In ADMOs, the metal ions reverse their positions to the oxygen ions [12].…”
Section: Introductionmentioning
confidence: 99%
“…topological behavior [5], ferromagnetic behavior [6][7][8][9][10] and thermoelectric transport properties [11,12]. In ADMOs, the metal ions reverse their positions to the oxygen ions [12].…”
Section: Introductionmentioning
confidence: 99%